2020
DOI: 10.1093/scan/nsaa107
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processes during deception about attitudes revisited: a replication study

Abstract: Event-related potential (ERP) studies about deception often apply recognition tasks. It remains questionable whether reported ERP patterns and cognitive processes can be generalized to other contexts. As the study by Johnson et al. (2008) fills this gap by investigating deception regarding attitudes, we tried to replicate it. Participants (N = 99) were instructed to lie or tell the truth about their attitudes. We obtained the same results as Johnson et al. (2008): lies were accompanied by enhanced medial front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…After the ring (item memory) is presented, the source memories of the guilty group and the knowledgeable innocent group are activated by stealing source words and other source words, respectively, while the source memories of the unknowledgeable innocent group are activated by neither stealing source words nor other source words. (2) Some studies showed that LPC could be regarded as P300 (Allen & Iacono, 1997; Farwell & Donchin, 1991; Johnson & Rosenfeld, 1992; Meijer et al, 2007; Scheuble & Beauducel, 2020b). A prerequisite for evoking the LPC/P300 is the presentation of small probability and/or meaningful stimuli (Johnson, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the ring (item memory) is presented, the source memories of the guilty group and the knowledgeable innocent group are activated by stealing source words and other source words, respectively, while the source memories of the unknowledgeable innocent group are activated by neither stealing source words nor other source words. (2) Some studies showed that LPC could be regarded as P300 (Allen & Iacono, 1997; Farwell & Donchin, 1991; Johnson & Rosenfeld, 1992; Meijer et al, 2007; Scheuble & Beauducel, 2020b). A prerequisite for evoking the LPC/P300 is the presentation of small probability and/or meaningful stimuli (Johnson, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the LPC was used to distinguish the guilty from both the knowledgeable innocent and the unknowledgeable innocent. Since there were no relevant studies and the LPC could be regarded as P300 (Allen & Iacono, 1997; Farwell & Donchin, 1991; Johnson & Rosenfeld, 1992; Meijer et al, 2007; Scheuble & Beauducel, 2020b), the SD value was also set to 5.46 μV when the BF was calculated during the statistical analysis on BSDF LPC , which could be convenient for comparing the detection efficiency of P300 with that of LPC. In addition, calculating BF requires the mean difference and standard error in each experimental condition in this study (Dienes, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…One tick at the xaxis stands for 100 ms and one tick at the y-axis for 1 µV. Adapted from Scheuble and Beauducel (2020a).…”
Section: Response-locked Grand Averages Of Fronto-central Electrodes ...mentioning
confidence: 99%
“…Pre-response positivities (PRP) showed smaller amplitudes for lies that suggested intentional monitoring was used in conjunction with the lies regarding attitudes. Lying about positively valued items is more cognitively demanding than lying about negatively valued items, as evidenced by the fact that MFN amplitudes increased and LPC amplitudes fell when lies were made about them 7 .…”
Section: Introductionmentioning
confidence: 99%